Designing a Project-Based Learning Worksheet: Validity and Feasibility Evidence from the Geometrocity Project - Wibowo, Fadhia Aliva; Rohati, Rohati; Nusantara, Duano Sapta; Kumalasari, Ade (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2026)
Students often struggle to express mathematical ideas through multiple external representations, particularly when learning polyhedral geometry that requires coordination of visual, verbal, and symbolic forms. This study aims to design a project-based learning worksheet and examine its validity and feasibility through the Geometrocity project. In this activity, students construct a miniature city as a contextual medium to explore geometric concepts while engaging with structured representational tasks. The study follows the ADDIE development framework and is limited to the development stage. The focus lies on producing a valid and feasible learning tool rather than measuring classroom effectiveness. Two material experts and one media expert evaluated the worksheet using validation instruments that assess content accuracy, language clarity, instructional presentation, and graphical design. Quantitative ratings were analyzed using descriptive statistics, while qualitative feedback supported iterative product revisions. The results indicate that the Geometrocity worksheet achieved high validity scores across all assessed aspects and met the criteria for feasibility. These findings suggest that the worksheet is suitable for use in further implementation studies. This study contributes a project-based worksheet that integrates structured representational activities within contextual geometry tasks.